Peran Kebijakan Politik Sektor Perdagangan Dalam Sertifikasi Halal Berdaya Saing Global - Dian Andamari Yekti; Chasnah Noer Setyani; Nur Milla; Mashudi Mashudi (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Indonesia holds the position as the largest Muslim country in the world, which is 87% of its total population (267 million people), so that this country is a decisive market in the world trade in halal products. The purpose of this study is to determine the role played by the political government on halal certification with the aim of global competitiveness. This study uses a literature study approach, and uses qualitative research methods that include some literature studies. The results of this study are expected for business actors to immediately obtain a halal certificate that the product is indeed halal, provide insight into the role of the government in the halal certification process.